Workplace mental health manual for nurse managers - Adams, Lisa Y., 1968- (Springer Publishing Company, 2015)
""This text provides a comprehensive overview, if not thesis, of the contributing factors to workplace stress and how to revisit [them] and our own mental health. How can nurses and health care workplaces expect to offer health and healing when such basic foundational human dynamics of mental health are not addressed? This work opens the door to both the dynamics and the deep dimensions of the root issues facing humanity and our places of work and play.""--Jean Watson, PhD, RN, AHN-BC, FAAN (From the Foreword)